Analysis of contextual variables in the evaluation of child abuse in the pediatric emergency setting - Ana Nunes de Almeida; Vasco Ramos; Helena Nunes de Almeida; Carlos Gil Escobar; Catarina Garcia (Elsevier, 2017)
Objective: This article comprises a sample of abuse modalities observed in a pediatric emergency room of a public hospital in the Lisbon metropolitan area and a multifactorial characterization of physical and sexual violence. The objectives are: (1) to discuss the importance of social and family variables in the configuration of both types of violence; (2) to show how physical and sexual violence have subtypes and internal diversity. Methods: A statistical analysis was carried out in a database (1063 records of child abuse between 2004 and 2013). A form was applied to cases with suspected abuse, containing data on the child, family, abuse episode, abuser, medical history, and clinical observation. A factorial analysis of multiple correspondence was performed to identify patterns of association between social variables and physical and sexual violence, as well as their internal diversity. Results: The prevalence of abuse in this pediatric emergency room was 0.6%. Physical violence predominated (69.4%), followed by sexual violence (39.3%). Exploratory profiles of these types of violence were constructed. Regarding physical violence, the gender of the abuser was the first differentiating dimension; the victim's gender and age range were the second one. In the case of sexual violence, the age of the abuser and co-residence with him/her comprised the first dimension; the victim's age and gender comprised the second dimension. Conclusion: Patterns of association between victims, family contexts, and abusers were identified. It is necessary to alert clinicians about the importance of social variables in the multiple facets of child abuse. Resumo: Objetivo: Este artigo apresenta uma casuística de modalidades de maus-tratos numa Urgência Pediátrica (UP) de um hospital público na Área Metropolitana de Lisboa e uma caracterização multifatorial da violência física e violência sexual. Os objetivos são: 1) discutir a importância de variáveis sociais e familiares na configuração de ambos; 2) mostrar como violência física e violência sexual apresentam subtipos e diversidade interna. Métodos: Realizou-se uma análise estatística de uma base de dados (1063 registos de maus-tratos infantis, entre 2004-2013). Utilizou-se o formulário aplicado a casos com suspeita de maus-tratos, com dados sobre a criança, família, episódio de maus-tratos, agressor, história médica e observação clínica. Foi realizada uma análise fatorial de correspondências múltiplas para identificar padrões de associação entre variáveis sociais e violência, física e sexual, bem como sua diversidade interna. Resultados: A prevalência de maus-tratos nesta UP foi de 0,6%. Predominam a violência física (69,4%) e a violência sexual (39,3%). Perfis exploratórios destes tipos foram construídos. Quanto à violência física, o sexo do agressor estrutura a primeira dimensão diferenciadora; sexo e grupo etário da vítima estruturam a segunda. No caso da violência sexual, a idade do agressor e coresidência com ele estruturam a primeira dimensão; idade e sexo das vítimas organizam a segunda dimensão. Conclusão: Identificaram-se padrões de associação entre vítimas, contextos familiares e agressores. É necessário alertar os clínicos para a importância das variáveis sociais nas múltiplas faces que os maus-tratos assumem. Keywords: Physical violence, Sexual violence, Children, Portugal, Hospital urgency, Palavras-chave: Violência física, Violência sexual, Crianças, Portugal, Urgência hospitalar